Peningkatan Kinerja Usaha Industri Retail Melalui Pendampingan Manajemen Sumber Daya Manusia Berbasis Pembagian Tugas dan SOP Kerja: Pengabdian - Theressa Taken Pasaribu; Aninda Puji Adila; Azolla Degita Azis; Restu Hanin Annisaa; Raihan Fajri Ramadhan; Budi Darma (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Improving retail business performance through human resource management mentoring based on task division and work SOPs aims to enable management at the Hombing Jaya store to distribute tasks in accordance with work SOPs and ensure work runs according to the wishes of the business owner and employees. This community service activity was conducted at one of the Hombing Jaya retail stores. This mentoring was conducted using a participatory approach and training conducted through observation and interviews, followed by discussions with participants. The results of this activity revealed that the Hombing Jaya store had not implemented a documented division of tasks, and that work was carried out solely based on habit, and that a work evaluation mechanism was not yet available. The implications of this community service are that participants are able to understand human resource management and equitable work division mechanisms, are able to create employee task divisions within the business, are able to establish performance SOPs, and evaluate performance in their business.